Networked Learning in Virtual Environments - Koubek, Anni; Kober, Sandra (Proceedings of the International Conference on Networked Learning, 2000)
Information and Communication Technologies (ICT) can support very well the learning process. However, one major drawback remains: the social dimension of learning can only be very poorely developed in a networked environment. The practical consequences of this fact are that most efficient learning strategies involve substantial time, where people meet physically in order to enable social learning processes. If this is geographically feasible, it definitly provides a solution for the problem. However, such meetings often involve substantial travel costs if learners are dispersed over countries or continents. The quest for new generation technologies is to eliminate this drawback of ICT and support social learning processes.